UNICEF Efforts to End Child Marriage in Nigeria 2020-2022 - Margie, Alycia; Sugara, Robi; Firnas, Muhamad Adian (STKIP Singkawang, 2024)
This study described the efforts made by UNICEF in addressing child marriage in Nigeria in 2020-2022. Nigeria is the fourth country with the most child marriages in West Africa in 2022. This study was written descriptively. The source of data used as material for analysis was taken from 2020-2022 and came from literature reviews in the form of reports official UNICEF documents and journal articles. The method used in this study was a qualitative method that was descriptive and analytical. The results of this study indicated that UNICEF's efforts to address child marriage in Nigeria had not fully addressed the practice of child marriage in Nigeria due to various factors and challenges such as traditions and culture in Nigeria and the time required to resolve the problem are not a few that hinder efforts being made.